The Effect of Human Development Index Components and Poverty on Economic Growth in Yogyakarta: Pengaruh Komponen Indeks Pembangunan Manusia (IPM) Dan Kemiskinan Terhadap Pertumbuhan Ekonomi di Yogyakarta - Khoirul Anwar; Rifki Khoirudin; Lusmino Basia (Institute of Educational, Research, and Community Service, 2023)
Economic growth is the most important component of Indonesia's national development because economic growth can be said to be a component that plays an important role in providing an assessment of economic performance. This research aims to determine the influence of the components of the human development index and poverty on the economic growth of the districts/cities of D.I Yogyakarta. This research uses secondary data sourced from the official website of the Central Statistics Agency. The data used is panel data, namely a combination of time series and cross section data. The appropriate model is the Random Effect Model. The variables used in this research are average years of schooling, life expectancy, per capita expenditure, number of poor people and minimum wage. The results of this research are that the life expectancy variable has a positive and significant effect on economic growth, per capita expenditure has a positive and significant effect on economic growth, while the average length of schooling has no effect on economic growth, the number of poor people has no effect on economic growth and the minimum wage has no effect. on the economic growth of the districts/cities of D.I Yogyakarta. Each independent variable significantly influences the dependent variable simultaneously